2016
DOI: 10.2106/jbjs.15.01080
|View full text |Cite
|
Sign up to set email alerts
|

Surgeons’ Accuracy in Achieving Their Desired Acetabular Component Orientation

Abstract: Surgeons overestimate operative inclination and underestimate anteversion, which is of benefit, as this, on average, helps to achieve the desired radiographic cup orientation. Although the use of visual cues helps, conventional techniques result in a large variability in acetabular component orientation. New and better guides and methods for training need to be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 21 publications
2
42
0
Order By: Relevance
“…Measures for apparent operative, true operative, radiographic, and neutralised radiographic acetabular orientation were obtained from the model. Variation in TAL version [24], surgical error [23] and pelvic orientation [9] were incorporated into the models to induce variation in the aforementioned measures. For each factor, normal distributions were fitted to clinical data from the literature and sampled randomly (n = 1,000).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Measures for apparent operative, true operative, radiographic, and neutralised radiographic acetabular orientation were obtained from the model. Variation in TAL version [24], surgical error [23] and pelvic orientation [9] were incorporated into the models to induce variation in the aforementioned measures. For each factor, normal distributions were fitted to clinical data from the literature and sampled randomly (n = 1,000).…”
Section: Discussionmentioning
confidence: 99%
“…Meermans et al [26] concluded that the TAL method was better at controlling radiological version based upon their radiographic outcomes being within the Lewinnek target zone. 21 Natural variation of TAL, [23] along with the natural variation in pelvic tilt, [13] may result in greater inter-patient variability with respect to measured radiological version. In this study, patientspecific targets for NRI and NRV were calculated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations